Potential Applications of Hydroxyapatite-Mineralized-Collagen Composites as Bone Structure Regeneration: a Review - Kushendarsyah Saptaji; Dindamilenia Choirunnisa Hardiyasanti; Muchammad Fachrizal Ali; Raffy Frandito; Tiara Kusuma Dewi (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2022)
The composites materials are known for their flexibility due to the combinations of two or three different materials and manipulation of their compositions. The advantage offered by composite materials make it suitable for biomedical applications especially to be used for implants. There are three types of composites biocompatible materials namely Metal Matrix Composite (MMC), Ceramic Matrix Composite (CMC) and Polymer Matrix Composite (PMC). In order to produce the biocompatible composite materials, various manufacturing processes can be performed. The manufacturing processes of MMCs are stir casting and powder metallurgy; the typical manufacturing process for CMCs is powder metallurgy; and 3-D printing by synthesizing and cross-linking the networks is used for fabricating PMCs. One of the promising biocompatible composites is Hydroxyapatite Mineralized Collagen (HMC). The HMC is used to create bone scaffold in bone regeneration process. The suggested manufacturing process for HMC is hybrid process which collaborate Additive Manufacturing and CNC Machining. In this paper, the HMC is reviewed especially related with its properties, fabrication method, and existed experimentation. In addition, the three types of biocompatible composites are also discussed on the applications and its manufacturing processes.